Beyond the employment agency: The effect of social capital on the duration of unemployment - Philipp Marek; Benjamin Damm; Tong-Yaa Su (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This paper relates an individual's social capital and the length of unemployment spells of the very same individual. For this purpose, we analyze several facets of an agent's social activities as determinants of her social capital. Social activities lead to social interactions within organizational settings, which build up social capital at the group level. Via social interactions an exchange of knowledge emerges, including information on opportunities to get a job. An econometric duration model based on German data is applied to empirically research the relationship between social capital and the duration of unemployment. Our results show that an individual's social capital positively affects an agent's probability to take up employment in the next time period. This implies social capital shortens the length of an unemployment spell significantly.
Keywords: Z13; J64; C41; 330; Social Capital; Job Search; Duration Analysis